Zadania opata określone w prawodawstwie monastycznym kręgu św. Fruktuoza z Bragi - Czyżewski, Bogdan Stanisław (Vox Patrum, 2020)
The article focuses on the monastic writings attributed to the circle of St. Fructuosus of Braga. One of them, Rule for the Monastery, was written by Fructuosus. Those works present an image of the monastic life on the Iberian Peninsula. In the organizational structure of the monastery the most important person was the abbot (abbas), whose duties are precisely defined in the Rules. He was to be of strict moral standards and have intellectual qualifications. He was responsible for the prayer in the monastery in his care, and individually for each monk. He often shared his duties with the superiors, which in some measure restricted his authority. The abbot also showed some democratic tendencies, in a sense imposed on him by the Rules. The abbot shared with the superiors and elders the responsibility for the monastic life, the abbot and the elders inflicted punishments on the monks, but important decisions were taken by the so-called council of brethren. Democracy in Fructuosian monasteries was also visible in the ties among them, involving abbots meeting, possibly once a month, in order to safeguard the common discipline in their subordinate monasteries.